1998
DOI: 10.1159/000044975
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Nephritogenicity of Two Monoclonal Antibodies That Recognize Different Epitopes ofRat Thy-1.1 Molecule

Abstract: The pathophysiological role of the Thy-1.1 molecule expressed on rat mesangial cells with regard to mesangial cell dysfunction and injury remains unknown. The mechanism of Thy-1.1-associated injury has now been investigated with two monoclonal antibodies, 1-22-3 and OX7, that recognize different epitopes of Thy-1.1. Mesangiolysis and mesangial cell proliferation were more marked in rats injected with 1-22-3 than in those treated with OX7. Immunostaining for rat complement component C3 and also C9 was similar i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
0

Year Published

1999
1999
2010
2010

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 36 publications
1
19
0
Order By: Relevance
“…A mouse monoclonal antibody to rat Thy-1 antigen (mAb1-22-3; 2 mg) or control (2 mg murine IgG in 1 ml saline) was intravenously administered to the rats. We used mAb1-22-3 because our previous data demonstrated that it was more effective than OX-7 in inducing mesangiolysis (25). Two days later (29), the rats were anesthetized with pentobarbital sodium (50 mg/kg ip) and placed on a thermostatically controlled heated table to keep body temperature at 37°C, as detailed previously (24,38).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A mouse monoclonal antibody to rat Thy-1 antigen (mAb1-22-3; 2 mg) or control (2 mg murine IgG in 1 ml saline) was intravenously administered to the rats. We used mAb1-22-3 because our previous data demonstrated that it was more effective than OX-7 in inducing mesangiolysis (25). Two days later (29), the rats were anesthetized with pentobarbital sodium (50 mg/kg ip) and placed on a thermostatically controlled heated table to keep body temperature at 37°C, as detailed previously (24,38).…”
Section: Methodsmentioning
confidence: 99%
“…We are aware of no in vivo studies examining effects of a mono-clonal anti-Thy-1 antibody on renal autoregulation. In the present study, we assessed the role of mesangial cells in in vivo renal autoregulation, comparing controls and Thy-1 nephritis induced by mAb1-22-3, another monoclonal antibody against Thy-1, which recognizes a Thy-1 epitope different from OX-7, one that is more nephritogenic than OX-7 (25).…”
mentioning
confidence: 99%
“…3 We have previously demonstrated that glomerular mRNA levels of type I and type IV collagens in a reversible model of mesangial matrix expansion increased on day 3, peaked on day 5 or 10, and then gradually decreased to normal levels. 4 Yagi et al 5 reported that glomerular mRNA levels of type I and type IV collagens increased on day 4, and then normalized by week 5 in a chronic model of GN. These findings indicate that impaired degradation, rather than the persistent synthesis of these collagens, is highly concerned with the development of chronic glomerular lesions.…”
Section: Introductionmentioning
confidence: 99%
“…The primary antibodies were rabbit anti-rat Thy-1.1 [9] (a hybridoma producing OX-7 IgG1 that was purchased from the European Collection of Animal Cells, Porton Down, Salisbury, UK) for the identification of glomerular mesangial cells, mouse monoclonal anti-rat ED-1 (Serotec Ltd., Kindlington, UK) for the detection of infiltrating macrophages, biotinylated anti-CD31 (Serotec Ltd.) for the identification of endothelial cells, and mouse monoclonal anti-rat endothelial nitric oxide synthase (eNOS; Abcam, UK). Tetramethyl rhodamine B isothiocyanate-conjugated goat anti-rabbit IgG, and fluorescein isothiocyanate-conjugated rabbit anti-mouse IgG (Dako, Denmark) were used as secondary antibodies.…”
Section: Methodsmentioning
confidence: 99%